Ritual Hogo Jako Dalam Pernikahan Adat Pada Kel. Gurabati ,Kota Tidore Kepulauan Perspektif ‘‘‘URF - Ratna A.Rachman; Ansar Tohe; Harwis (Global Action and Education for Society, 2026)
The Hogo Jako ritual is an old tradition in customary marriages in Tidore. It is considered a way to cleanse oneself and ward off misfortune before starting married life. However, this practice has now declined due to social changes and mixed marriages. Therefore, it is important to study the process and its position from the perspective of ‘urf so that the understanding of tradition and its boundaries within Islamic law becomes clearer. This study aims to explain the process of the Hogo Jako ritual in customary marriages in Tidore and to assess its legal status from the perspective of ‘urf. This research uses a descriptive-analytical qualitative approach with fieldwork in Kelurahan Gurabati, South Tidore District, Tidore Islands City, from November 2024 to February 2025. Data were collected through observation, interviews, and documentation. The analysis was conducted deductively through the stages of reduction, presentation, and drawing and verifying conclusions. The validity of the data was strengthened through triangulation and discussions with peers or supervisors. The results of the study show that Hogo Jako is a bathing ritual for the bride and groom before the marriage contract to repel misfortune and achieve spiritual cleansing. The ritual is accompanied by symbols and prayers for the couple. The procession is usually held at the bride’s home, involving a female traditional figure (yaya se goa), with the use of water and certain plants as part of the ritual equipment. From the perspective of Islamic law, this ritual is included as ‘urf ‘amali and is considered valid (‘urf shahih) because it does not contradict the Qur’an and Sunnah and does not cause harm. The study also notes the decreasing practice of this ritual, influenced by mixed marriages and social change.